(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
The current study highlights the linguistic errors in morphology and syntax written assignments committed by the English-major students at Salahaddin University-Erbil. This investigation, as the title refers to, is restricted to the analysis of errors at sentence-level. The analysis is applied to certain respects which encompass 1) categories of errors that are composed of grammatical, semantic, morphological, spelling, and punctuation errors, 2) error rates for each category, 3) error sources and 4) the percentage of the frequency of each error source. The analysis of discourse-level errors is excluded as it is beyond the scope of this research. To conduct a study into the intended learners’ errors, a sample of 80 randomly selected students were given the task of writing answers to morphology and syntax short-answer questions. The results obtained from the analysis revealed that grammatical errors, among other categories of errors, were the most commonly occurring errors. The analysis additionally found out that 1) inter-lingual factors, 2) intra-lingual factors and 3) students’ inclination to prefer efficient communication to accuracy were almost equally responsible for students’ errors. The analysis results provided bases for suggesting remedial measures and teaching strategies that could assist EFL teachers in dealing effectively with students’ errors.